2019
DOI: 10.1016/j.ijhm.2018.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of consumer experience formulation in the sharing economy

Abstract: The study examines the complexity of the factors that influence overall perception among tourists who use peer-to-peer accommodation during their vacations. More specifically, it employs fuzzy-set Qualitative Comparative Analysis to analyse data from a sample of 712 peer-to-peer holidaymakers visiting Athens, Greece, and examines the socio-demographics of age and income along with the simple attributes of perceived risks, marketing and advertising, social aspects, and price and quality issues. The findings rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 80 publications
2
51
0
1
Order By: Relevance
“…For personal satisfaction, for example, Nov et al [30] found that this type of motivation, expressed in the satisfaction of sharing photos, incentivized a great number of those adept in social networks to participate in online communities. Pappas [26], on the other hand, determined that enjoyment, measured in terms of social interaction, positively impacts the experience of a tourist who opts for shared accommodation services. Regarding sustainability, Kim et al [31] and May et al [52] demonstrated that non-selfish factors (for example, interest in helping others or protecting the environment) appear to occupy a dominant role in the intention to participate in collaborate initiatives.…”
Section: Anova Test Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For personal satisfaction, for example, Nov et al [30] found that this type of motivation, expressed in the satisfaction of sharing photos, incentivized a great number of those adept in social networks to participate in online communities. Pappas [26], on the other hand, determined that enjoyment, measured in terms of social interaction, positively impacts the experience of a tourist who opts for shared accommodation services. Regarding sustainability, Kim et al [31] and May et al [52] demonstrated that non-selfish factors (for example, interest in helping others or protecting the environment) appear to occupy a dominant role in the intention to participate in collaborate initiatives.…”
Section: Anova Test Results and Discussionmentioning
confidence: 99%
“…In addition to the aforementioned, the studies carried out in this field have opted for an analysis of concrete initiatives that have circumscribed the scope of their results in a specific segment. According to the literature review (see Appendix A), the vast majority of studies focus on motivations, have opted to analyze specific collaboration or exchange activities (90%), like car sharing, room sharing, open source projects or virtual communities [26][27][28].…”
Section: Research Gaps About CC From a Motivations Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…Review papers [2][3][4] and edited books [5,6] outline some of the research topics undertaken in these studies. These include competition between peer-to-peer rentals and traditional hospitality industry [7][8][9][10][11], general contribution to destinations' economies [12][13][14], social impacts [15][16][17][18], with special attention given to the impact on housing markets [19][20][21][22][23], policy and regulations on P2P rental platforms [24][25][26][27], costumer satisfaction of the service provided [28][29][30] and the impact of these new practices on travel patterns [31].…”
Section: Introductionmentioning
confidence: 99%